The Validity of Reconciliation Without Witnesses at The Religious Affairs Office: Keabsahan Rujuk Tanpa Saksi Di Kantor Urusan Agama - Mukdin, Khairani; Izzati, Rahmil; Syuhada, Syuhada (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2023)
Some factors in establishing a family can result in divorce. Islam permits a husband and wife to reconcile during the iddah period (a specified period of time that must elapse before a Muslim widow or divorcee may legitimately remarry). In accordance with this requirement, a husband who wishes to reconcile with his ex-wife must go through the Religious Affairs Office (KUA) and adhere to the established protocols. However, the practice is different, as happened in the KUA of Syiah Kuala Subdistrict, Banda Aceh, which carried out the reconciliation process without witnessing. Contrarily, it is explicitly stated in The Compilation of Islamic Law (KHI) articles 163–169 that witnesses are necessary in cases involving reconciliation. According to the KUA, the process for reconciliation is that the husband who wants to get his wife back comes to the marriage registrar who oversees the neighborhood where the husband and wife reside by bringing a stipulation about the possibility of divorce and the required certificate, which is followed by reconciliation in front of the registrar and witnesses. It is not necessary for witnesses to be present. The most important aspect is that the community be aware of their reconciliation, whether or not they are present. Upon that, a reconciliation certificate is created and delivered to the religious court where the divorce occurred. They view reconciliation as a continuation of the marriage, not a new marriage contract, which explains why there are no witnesses in the process of reconciliation cases. Therefore, in the process of reconciliation, witnesses are not as crucial. KHI, however, demands a witness to the reconciliation for the purpose of benefit. The reconciliation is deemed unlawful without a witness because permanent law cannot be established. Even without witnesses, the KUA can issue a certificate of reconciliation, which is accepted by the court to consider the reconciliation valid.